The manifestations of the volition philosophy in the mind of al-Farabi - Hannawi, Nadia (Journal of Oriental Studies, 2020)
This research revolves around the philosophy of will that Paul Ricour has been looking at. The focus of this philosophy is the human error, which is based on a number of concepts, including five: infallibility and incongruity, mixture and mediator, the idea of the universal, the impact of misery, infinity Dozens of books and hundreds of studies and research papers have been written in Al-Farabi’s philosophical legacy, and various methodologies and ideological, sociological, anthropological and political propositions have been formulated around it, and theories have been developed in it, some of which are literary and intellectual and others are psychological, social and cultura .Each of these concepts is based on intellectual constructs and procedural representations that deal with issues of thought and existence. This research attempts to reconcile these five concepts and the ideas of the philosopher Abu Nasr al-Farabi (339 e) by shedding light on some of his books and letters. Key words: Concept, Al-Farabi, Philosophy, Ricor, volition.